Compendium of International and National Legal Frameworks on Child Marriage - Calimoutou, Emelyne; Liu, Yuantao; Mbu, Beverley (Washington, DC: World Bank, 2017)
The Compendium of International and National Legal Framework on Child Marriage (‘the Compendium’) provides a survey of the key international, regional and national legal instruments as they relate to the right to marry with the full and free consent of the intending spouses and to the obligation for government to take legislative measures to abolish child marriage. The Compendium consists of topical chapters with jump links to source documents, such as United Nations conventions, regional treaties, national constitutions and legislations.